THE INSTITUTE OF ADOPTION IN THE RUSSIAN FEDERATION - Asmik A. Aleksanyan (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
In present day Russia hundreds of thousands of children are left without parents' care due to different circumstances. The article presents various opinions of Russian academics concerning adoption in the Russian Federation. The topicality of this issue is explained by the fact that adoption is one of the most important institutions. These relations require more detailed research as adoption is a priority form of settlement for children left without parents' care. The author shows the significance of the adoption institution, which is multisided. She gave and analyzed statistics, which could help investigate the adoption institution in the Russian Federation.